2021
DOI: 10.1088/1475-7516/2021/03/030
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum of intrinsic alignments of galaxies in IllustrisTNG

Abstract: We present the 3-dimensional intrinsic alignment power spectra between the projected 2d galaxy shape/spin and the 3d tidal field across 0.1<k/<60 using cosmological hydrodynamical simulation, Illustris-TNG300, at redshifts ranging from 0.3 to 2. The shape-tidal field alignment increases with galaxy mass and the linear alignment coefficient AIA, defined with respect to the primordial tidal field, is found to have weak redshift dependence. We also show a promising detection of the shape/spin-tidal field al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…The column "σ " in Table 1 gives the intrinsic rms ellipticities for the new method (Eq. 1), showing that the new method gives a larger σ ∼ 0.4 than that of the usual method, σ ∼ 0.3 as shown in Shi et al (2021). The IA power spectrum between matter density field δ m and E-mode shear field γ E is estimated following the method in Kurita et al (2021):…”
Section: An Aperture Shape Estimator For Elgsmentioning
confidence: 96%
See 2 more Smart Citations
“…The column "σ " in Table 1 gives the intrinsic rms ellipticities for the new method (Eq. 1), showing that the new method gives a larger σ ∼ 0.4 than that of the usual method, σ ∼ 0.3 as shown in Shi et al (2021). The IA power spectrum between matter density field δ m and E-mode shear field γ E is estimated following the method in Kurita et al (2021):…”
Section: An Aperture Shape Estimator For Elgsmentioning
confidence: 96%
“…Observationally, several studies have shown a significant detection of the IA effect for luminous red galaxies up to z ∼ 0.7 (Mandelbaum et al 2006;Hirata et al 2007;Okumura & Jing 2009;Singh, Mandelbaum & More 2015;Singh & Mandelbaum 2016). In contrast, jingjing.shi@ipmu.jp there is no clear signature of the IA effect reported for blue star-forming galaxies from data (Mandelbaum et al 2011;Tonegawa et al 2018;Yao et al 2020) nor from simulations (Chisari et al 2016a;Tenneti, Mandelbaum & Di Matteo 2016;Shi et al 2021). Star-forming galaxies are useful tracers of large-scale structures up to the higher redshifts, and indeed main targets for upcoming wide-area galaxy redshift surveys such as the Subaru Prime Focus Spectrograph (PFS) survey (Takada et al 2014) and the DESI survey 1 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike the first one, however, the second question still awaits a conclusive answer, which requires expensive high-resolution cosmological hydrodynamical simulations. While several works reported that the alignment tendencies of the galaxy stellar spins with the local filaments were found similar to those of DM spins at low redshifts z ≤ 0.5 (e.g., Wang et al 2018;Kraljic et al 2020), several others claimed that the nonlinear baryonic process responsible for the deviation of the galaxy stellar spin directions from those of DM counterparts must have completely destroyed any tidal connection, randomizing the galaxy stellar spin vectors relative to the local filaments at z ≤ 0.5 (e.g., Codis et al 2018;Ganeshaiah Veena et al 2019;Shi et al 2021). The difference in the identifications of the filaments has been suggested as a possible reason for the discrepant results Kraljic et al (2020).…”
Section: Introductionmentioning
confidence: 94%
“…Duffy et al 2010;Schaller et al 2015a;Springel et al 2018). Hydrodynamical simulations have been used to study the intrinsic alignment of galaxies even well within the non-linear, one-halo regime (Chisari et al 2015(Chisari et al , 2016Codis et al 2015;Tenneti et al 2015;Velliscig et al 2015b;Hilbert et al 2017;Harvey et al 2021;Shi et al 2021). They offer a means to obtain physical insights into the origins of galaxy shape correlations, and to assess the accuracy of analytic alignment models (Samuroff et al 2021).…”
Section: Introductionmentioning
confidence: 99%